Hubungan antara Self-Control dan Toxic Disinhibition Online Effect pada Mahasiswa yang Menggunakan Sosial Media - Ruli Gustian Nugraha; Kristin Rahmani; Heliany Kiswantomo; Dinta Nurannisa Aliifah; Alryami Rahma Pusti (Universitas Kristen Maranatha, 2023)
The emergence of the internet in the current era has transformed the paradigm of students in their interactions, learning, and even coordinating collective actions. The Internet provides convenience in the exchange of ideas and information, as well as facilitating fast, easy, and accessible communication for various segments of society. New forms of social interaction through the internet have enriched both personal and social life on a broader scale. However, despite the significant constructive potential of the internet, there is another aspect that needs attention. The internet has the potential to reinforce communication behaviors that are inappropriate, less suitable, or even unrestricted, often referred to as the